COMPARATIVE ANALYSIS OF PHYSICAL PARAMETERS OF RR LYRAE - Romanov, Yu. S.; Zgonyaiko, N. S.; Vasilyeva, S. V. (Одеські астрономічні публікації, 2017)
For analysis of spectral observations of RR Lyrae obtained by Butler in 1974 with a dispersion of 8 Å/mm, a two-component "curve-of-growth" method is used which has been developed at the Odessa Astronomical Observatory. As a result, a number of physical parameters are obtained as well as their phase variations: temperature, spectral type, electron pressure, turbulent velocity. Parameters of Tex and lg Pe have proved to be somewhat higher than the values found by Butler and correspond to the B9.1 - F0.9 range typical of this stellar spectral type.